Ladder 49 - Russell, Jay, 1960-; Phoenix, Joaquin; Travolta, John, 1954-; Chestnut, Morris; Patrick, Robert, 1958-; Getty, Balthazar; Carter, James L.; Ross, William, 1948-; Touchstone Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) ([United States] : Touchstone Home Entertainment ; Burbank, CA : Distributed by Buena Vista Home Entertainment, 2005)
Probationary firefighter Jack Morrison matures into a seasoned veteran of the Baltimore Fire Department under the watchful eye of his mentor Chief Mike Kennedy. Responding to the worst blaze in his career, he becomes trapped inside a 20-story building. As Jack reflects on his life - seeing his first fire, bonding with fellow firefighters, the impact his job has had on his wife and kids - Chief Kennedy frantically coordinates the effort to save Jack's life.
Title from container.
English track
Originally released as a motion picture in 2004.
English track: Dolby digital 5.1.
French track: Dolby digital 5.1.
Commentary: Dolby digital 2.0.
Keywords: Baltimore (Md.). -- Fire Dept. -- Drama; Fire fighters -- Maryland -- Baltimore -- Drama; Fire extinction -- Drama; Lifesaving at fires -- Drama; Feature films; Films for the hearing impaired